Integration of the Al-Qur'an and Science to Improve the Intellectual Intelligence of Graduate Quality - Baihaqi Aziz; M Maskuri; Dian Mohammad Hakim (PT Mattawang Mediatama Solution, 2026)
In the era of globalization, science is dominated by the West, while the contribution of Muslims is often considered minimal. SMA Trensains Tebuireng 2 Jombang integrates the Qur’an and science into the curriculum to improve students’ religiosity and intellectual intelligence. This study aims to examine the verses of the Qur’an, the process, and the science integration model to enhance graduates’ quality. With a qualitative phenomenological approach, data were obtained through observation, interviews, and documentation. The results show integration based on verses such as QS. Al-Syu’ara: 4, QS. Al-Rum: 25, and QS. Al-Insan: 17, which discusses creation and natural phenomena. The process involves a thematic curriculum, an approach to scientific interpretation, and discussion-based learning and presentations. Supporting factors include laboratories, libraries, and institutional support, although constrained by limited human resources and media. This integration model is efficacious in improving intellectual intelligence and religiosity, producing superior graduates based on Islamic values.